2016
DOI: 10.1590/s1808-185120161501153517
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Sagittal Balance on the Clinical Outcome in Spinal Fusion

Abstract: Objective: Evaluates which radiographic parameters of the sagittal and spinopelvic balance influence the clinical and functional outcomes of a sample of patients undergoing spinal fusion. Methods: We studied 32 patients who underwent spinal fusion. Radiographs of the total spine were obtained from all patients. The clinical and functional parameters studied were analysis of pain by visual analogic scale (VAS) and Oswestry and SRS-30 questionnaires. We analyzed the correlation between the clinical and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The spinopelvic morphology modulates the lumbosacral configuration and consequently, the mechanical stress at the lumbosacral junction. Restoration of the sagittal balance has been emphasized recently (33,54) and it has been shown to directly impact both the standing balance and clinical outcomes of the patients (54,55). Kawakami et al (56) studied whether lumbar sagittal balance affected the clinical outcome after PLF and they concluded that SVA (center in the L1 to the back corner of the S1) should be considered in the choice of treatment strategy when PLF is indicated for patients with degenerative lumbar spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The spinopelvic morphology modulates the lumbosacral configuration and consequently, the mechanical stress at the lumbosacral junction. Restoration of the sagittal balance has been emphasized recently (33,54) and it has been shown to directly impact both the standing balance and clinical outcomes of the patients (54,55). Kawakami et al (56) studied whether lumbar sagittal balance affected the clinical outcome after PLF and they concluded that SVA (center in the L1 to the back corner of the S1) should be considered in the choice of treatment strategy when PLF is indicated for patients with degenerative lumbar spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The published studies on functional outcome and SPA after spinal surgery have offered conflicting results. A number of studies have established a significant relationship between these parameters and outcomes, while others were unable to establish a relationship, even with positive outcomes, while these measurements were abnormal [2,3,7,10,12,[14][15][16]. This inconsistency may be due to other factors contributing to the outcome not being studied or due to the short follow-up procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The spino-pelvic parameters are key components in the evaluation and treatment of sagittal deformities 9 and also of degenerative pathologies of the spine, as correct sagittal alignment directly impacts the quality of life of these patients. 13,14 The current standard for acquiring the measurements uses manual measuring of these parameters with a goniometer, a process that requires a dermatograph pencil for drawing lines on the radiographic film, as well as the goniometer itself, which the clinician many times does not have on hand. 15 Recently, with the inclusion of technological tools in medical practice, these technologies can be used to assist physicians in clinical practice.…”
Section: Introductionmentioning
confidence: 99%